Shaping Future Directions for Breakdance Teaching - Wei, Ming Tao; Yang, Zhi; Bai, Yu Jie; Yu, Ning; Wang, Chun Xia; Wang, Nan; Cui, Yan Shuo (Frontiers in Psychology, 2022)
This article reports on the evolution of breakdance. Given the inclusion of breakdancing in the 2024 Olympic Games in Paris, France, scholars have generated substantial international research related to breakdance teaching in recent years. However, few researchers have focused on the impact of formative assessment on breakdance teachers' teaching and students' learning. We wish to contribute to promote the quality of breakdance teaching and learning by identifying the positive impact of recent research on formative assessment on student learning and designing a formative assessment task related to breakdance. This article lays out a framework of formative assessment tasks and identifies the positive impact of formative assessment on dance education. It concludes with a call to dance schools to begin to integrate formative assessment into breakdance curricula and practice experiences.